Rereading the Concept of Joint Property: Fiqh Literacy in the Book of Sabilal Muhtadin and the Genealogy of Sheikh Arsyad's Thoughts - Tarantang, Jefry; Akbar, Wahyu; Astiti, Ni Nyoman Adi; Rollis, Rollis; Ridwan, Ahmad Hasan (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2024)
This research describes fiqh literacy regarding joint property which has become an academic rumor referring to the Book of Sabilal Muhtadin by Sheikh Arsyad, which is a reference for studies on joint property in Indonesia. Because of this, it is necessary to re-read the concept of joint property, which was born from the culture of the Banjar people, namely the property of taboo, which was initiated by Sheikh Arsyad, because the reference is not from the Book of Sabilal Muhtadin.This research uses a type of normative research using historical, hermeneutic, netnographic, conceptual and philosophical approaches. Data was collected by means of literature studies that refer to the book of Sabilal Muhtadin and articles and studies of parties who are concerned about the book in correspondence. The findings of this research indicate that the Islamic legal methodology used by Sheikh Arsyad regarding the concept of joint property is a product of his ijtihad taking into account the local culture of the Banjar community. Although there is a misrepresentation of fiqh literacy regarding joint assets in the Sabilal Muhtadin Book which is used as a literary reference. Sheikh Arsyad's genealogical thoughts regarding joint property, although not contained in Sabilal Muhtadin's Book, have become a local legal doctrine that has been transformed into a global insight using the methods of islah, maslahah mursalah, urf, and adatul muhakkamah.However, this concept will not be degraded, because it has been practiced for a long time and has become a living law that contains beneficial values.